Data superstream. (O'Reilly Media, Inc., 2023)
The ability to store, process, and manage data in the cloud efficiently and cost-effectively is a must for working with today's enormous datasets. Data lakes answered the problem of silos found in many data warehouses. And the data lakehouse emerged as a solution that combined the strengths of both models. But with the number of versatile data storage and management options available, it can be hard to figure out which solution is right for you. These expert-led sessions will give data engineers, software engineers, and solution architects insight into how to increase the scalability, speed, and availability of your data, along with best practices for best utilizing your data warehouse, data lake, or data lakehouse. About the Data Superstream Series: This Superstream series is designed to help your organization maximize the business impact of your data, and packed with insights from key innovators and the latest tools and technologies to help you stay ahead of it all. What you'll learn and how you can apply it Get an overview of the latest technologies for storing and managing your data Discover the benefits of implementing a data lakehouse for improved analytics and data science Understand how to perform robust analytics on a cloud data warehouse Find out how to test data quality at scale with Apache Iceberg Learn best practices for using a data mesh approach Explore how to democratize and leverage machine learning on a data lakehouse This recording of a live event is for you because... You're a data or software engineer or solution architect interested in learning about the latest trends in storing, processing, and managing data. You want to improve the scalability, speed, and availability of your data. You want to better understand the systems that you already use and learn how to take full advantage of their capabilities. Recommended follow-up: Read The Cloud Data Lake (book) Read Data Management at Scale, second edition (book) Take Google BigQuery First Steps (live online training course with Joy Payton) Take Data Lakehouse Fundamentals (live online training course with Janani Ravi) Please note that slides or supplemental materials are not available for download from this recording. Resources are only provided at the time of the live event.